The usage of communication technology media in household: How far is it gendered-neutral? / Nurulizzah Mohamed - Mohamed, Nurulizzah (Universiti Teknologi MARA Cawangan Pahang, 2002)
The effects of a technology are not only determined by its production, physical and capability, but they also depend on how they are consumed. Many people see technology as 'the material of male power', rather than neutral. In this paper, I am going to focus only on one example of the communication technology media, which is the telephone. Based on my research, I found out that the usage of the telephone in the household is not gender neutral.